Maulana Fazal-ur-Rehman as An Alliance Maker: A Case Study of Pakistan Democratic Movement - Zafar, Muhammad Naeem; Arshad, Farooq; Ali, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
Pakistan has a history of opposition alliances. Purpose of this article is to evaluate the role of Pakistan Democratic Movement in Pakistan. Maulana Fazal-ur-Rehmanis the president of the Pakistan Democratic Movement and Jamiat Ulema-e-Islam. On September 20, 2020, the PDM was established. The coalition was formed from 11 political parties. Slogan of PDM was to respect the sanctity of the vote. In 2022, the PDM formed a government under the leadership of opposition leader Shehbaz Sharif after successfully ousting Khan in a no-confidence resolution on April 10th.Maulana Fazal-ur-Rehmanannounces 12-Point Charter of Pakistan. In addition, Rehman said that Khan was backed by Jewish lobby, agent ofQadianes, Jews, and Americans. Protests against inflation were announced by the PDM.Under the leadership of the PDM, Pakistan was able to successfully remove itself from the FATF grey list. The administration of the PTI did not assume political ownership of the CPEC project in the same way that previous governments led by the PML-N had done so. The government of PDM is the responsible for historic economic woes.